2018
DOI: 10.1016/j.jpainsymman.2017.12.476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indicators for Achievement of Pain Control With a Personalized Pain Goal in a Comprehensive Cancer Center

Abstract: The achievement of PPG was a stricter pain relief indicator than PI and interference and may reflect a real need for pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Approximately half of the participants achieved PPG during the observation period. Several studies have reported PPG achievement rates of approximately 30-50%, similar to that observed in this study [25,26]. It has also been suggested that with appropriate opioid dose adjustment, pain is controlled within 7 days in most patients.…”
Section: Discussionsupporting
confidence: 86%
“…Approximately half of the participants achieved PPG during the observation period. Several studies have reported PPG achievement rates of approximately 30-50%, similar to that observed in this study [25,26]. It has also been suggested that with appropriate opioid dose adjustment, pain is controlled within 7 days in most patients.…”
Section: Discussionsupporting
confidence: 86%
“…In a qualitative study of clinician descriptions of pain goals, Gibbins et al 24 reported that clinicians assumed they understood patient's goals for function. In a pilot study using nurse-led motivational interviewing to set functional pain goals, Ehrlich et al 16 established that patients receiving palliative care were able and willing to make functional pain goals, which were specific goals for what mattered when cancer pain was controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of PPG was defined as achieving an average PI lower than or equal to the PPG (PI ≤ PPG) in the previous 24 hours (20,25).…”
Section: Ppg Achievementmentioning
confidence: 99%